Parry-Romberg Syndrome: a Rare Case Report - Anusha Laxman Rangare; Subhas Gogineni Babu; Priya Sara Thomas; Shishir Ram Shetty (eJournal of Oral Maxillofacial Research)
Background: The purpose of this report is to present a rare entity of Parry-Romberg syndrome. This poorly understood degenerative condition is characterised by atrophic changes affecting one side of the face. The cause of these changes remains obscure.Methods: The authors report one rare case of a 31 year old female patient with Parry-Romberg syndrome, accompanied by a brief review of literature.Results: Clinical examination of the patient revealed evident facial asymmetry, malar hypoplasia, atrophy of skin and other tissues on the left side, hyperpigmentation of skin on the left side of the face. Final diagnosis of a Parry-Romberg syndrome (“progressive hemifacial atrophy”) was based on thorough clinical and a radiological examination. Treatment using alloplastic implants to improve facial disfigurement was suggested to the patient.Conclusions: In most cases, Parry-Romberg syndrome appears to occur randomly for unknown reasons. The pathophysiology of the syndrome remains unknown. There is no definitive treatment for this condition but an attempt to use restorative plastic surgery which includes fat or silicone implants, flap/pedicle grafts, or bone implants can be done to improve facial disfigurement.